Insuficiencia de medios probatorios en el juicio de simulación en el derecho ecuatoriano - Borja Moya, Esteban Sebastián (2015)
The present work, is a study about the simulation of acts with effects on law, the action itself and the means of proof that must be used in a trial on simulation. The reader will be able to find the concept of simulation as it were developed by numerous experts, concept that has evolved on time, and the fundamental elements for distinction between a simulation and a real act, along with classified types of simulation. The absence of a specialized norm on relation with simulation, makes the simulated action hard to judge, so to our criteria the proposal of law that is presented on this work meets the requirements to be used on Ecuador. Simulation is generally confused with other close figures, which have been studied particularly. We have exposed the differences with simulation for a better understanding. The proof on the trials about simulation is critical. Simulation is considered hard to be proved because of the cleverness of the simulators. It is almost impossible for the person that has the interest on the declaration of a simulated act to find a direct and efficient proof. Therefore, on this work the reader can find the parameters to conduct an efficient research and obtain the means to prove by indirect proof that the act was simulated. It has been specified a guide on which, lawyers that are seeking for the act to become decelerated a simulation can base on.